Long-term decline in egg size of Atlantic puffins Fratercula arctica is related to changes in forage fish stocks and climate conditions - Barrett, Robert T.; Nilsen, Erlend Birkeland; Anker-Nilssen, Tycho (Marine Ecology Progress Series, 2012)
Due to major shifts in the marine ecosystem, many seabirds in the NE Atlantic have experienced short- and long-term breeding failures and population changes. One such seabird is the Atlantic puffin Fratercula arctica, the populations of which have declined in Norway at an annual rate of 2% over a ~30 yr period. Parallel to this decline, we found a significant decline in egg volume at 2 widely separated Norwegian colonies situated in different marine ecoregions, a decline that is unprecedented among auks. In birds, egg production is costly for the female and varies in response to the amount of energy available for reproduction. Whereas proximate factors determining egg size are largely unknown, food availability prior to egg-laying is considered important. Using generalised least-square models, we demonstrate that the declines in egg size were driven by interannual changes in abundances of capelin Mallotus villosus and early life stages of herring Clupea harengus and haddock Melanogrammus aeglefinus, all of which are important prey of Atlantic puffins in these colonies. Furthermore, changes in climatic variables, such as sea temperature and the North Atlantic Oscillation, suggest that other prey may also have played a role in determining puffin egg size. The decline in egg size may reduce the quality of future breeders and hence have negative effects on puffin populations.